Corporate social responsibility in the multinational enterprise: strategic and institutional approaches - Husted, Bryan W; Allen, David B (Journal of International Business Studies, 2006)
What is the relationship of global and local (country-specific) corporate social responsibility (CSR) to international organizational strategy? Applying the strategic logic of the Bartlett and Ghoshal typology to the realm of CSR, multinational firms should respond to pressures for integration and responsiveness from salient stakeholders. However, an institutional logic would suggest that multinational firms will simply replicate the existing product-market organizational strategy (multidomestic, transnational, global) in their management of CSR. These alternative approaches are tested with a survey instrument sent to MNEs operating in Mexico. The results of this study are consistent with the proposition that institutional pressures, rather than strategic analysis of social issues and stakeholders, are guiding decision-making with respect to CSR. We develop implications for MNE management and research, as well as public policy.